Learning cardiology echocardiography, cineangiography. - Steinzeig, Sherman M.; University of Kansas. School of Medicine (Webster, TX : Studymed Software, 1999)
Covers coronary artery disease with emphasis on cineangiography and valvular heart disease with emphasis on echocardiography.
This program was written using Multimedia Toolkit 6.5.
Catalog number: 717-9146.
System requirements: a Pentium PC using Microsoft Windows 3.1 or higher with Mplayer.exe or Mplay32.exe.
Keywords: Cardiology; Echocardiography; Cineangiography; Heart -- Diseases -- Diagnosis